Modeling of Tourist Satisfaction in Bali - Adinegara, Gusti Ngurah Joko (Bina Nusantara University, 2018)
This research provided the new results on the determinants of tourist satisfaction. The data were obtained using questionnaire as the instrument. The variables used were destination and hotel service quality, destination and hotel image, tourist perceived value, tourist satisfaction, revisit intention, and word of mouth. Sampling technique was convenience sampling. The respondents were foreign and domestic tourists who traveled to Bali and stayed at three and four-star hotels. The sample size was 265. Then, the Structural Equation Modeling (SEM) was utilized in explaining the relationship between latent variables and hypotheses. The result shows that from eleven hypotheses, there are two rejected hypotheses regarding the influence of destination service quality and hotel service quality on the image. Destination and hotel image has a significant effect on revisit intention and word of mouth through tourist perceived value and satisfaction. Theoretically, tourist satisfaction determines the factors that affect it directly and indirectly. Practically, tourism business should manage the destination and hotel service quality because it increases the tourist perceived value.